Strengthening primary health-care services to help prevent and control long-term (Chronic) non-communicable diseases in low- and middle-income countries - Haque, Mainul; Islam, Tariqul; A. Rahman, Nor Azlina; McKimm, Judy; Abdullah, Adnan; Dhingra, Sameer (Dove Medical Press Ltd, 2020)
The prevalence of long-term (chronic) non-communicable diseases (NCDs) is increasing globally due to an ageing global population, urbanization, changes in lifestyles, and inequitable access to healthcare. Although previously more common in high- and upper-middle-income countries, lower-middle-income countries (LMICs) are more affected, with NCDs in LMICs currently accounting for 85- 90% of premature deaths among 30- 69 years old. NCDs have both high morbidity and mortality and high treatment costs, not only for the diseases themselves but also for their complications. Primary health care (PHC) services are a vital component in the prevention and control of long-term NCDs, particularly in LMICs, where the health infrastructure and hospital services may be under strain. Drawing from published studies, this review analyses how PHC services can be utilized and strengthened to help prevent and control long-term NCDs in LMICs. The review finds that a PHC service approach, which deals with health in a comprehensive way, including the promotion, prevention, and control of diseases, can be useful in both high and low resource settings. Further, a PHC based approach also provides opportunities for communities to better access appropriate healthcare, which ensures more significant equity, efficiency, effectiveness, safety, and timeliness, empowers service users, and helps healthcare providers to achieve better health outcomes at lower costs.